LIFE SKILL EDUCATION IN BUILDING THE INDEPENDENCE OF STUDENTS AT PONDOK PESANTREN FATHUL ULUM JOMBANG - Ikfi Khoulita; Siti Khoirun Nisak; Khoirun Nisa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The aim of this research is to examine life skills education at Pondok Pesantren Fathul Ulum Jombang. This research is particularly interesting because, as a pesantren still using the salafiyah learning model, life skills education is an inseparable part of the curriculum. The research uses a qualitative method, with data collection through interviews, observation, and documentation. The analysis is descriptive. The results of the study show that the life skills education provided at Pondok Pesantren Fathul Ulum Jombang is fascinating due to its unique approach. Students who enter the Aliyah level are required to choose one of the available majors, one of which is the